Exploring the Practice of Code Switching by Lecturer in English Speaking Class - Agustina, Mara; Widagsa, Rudha (Universitas PGRI Yogyakarta, 2024)
In teaching-learning English, lecturer commonly switch to their native language to ensure students understand the material this phenomenon is known as code switching. Code switching is the phenomenon where the speaker speaks use one language and switch to other language. This study aimed to figure out types and functions of code-switching and purposes of lecturer used code-switching in the teaching-learning process. This study was qualitative research used thematic analysis data to collected the types, functions of code-switching also purposes of lecturer’s code-switching. The study findings three different types of code-switching (a) tag-switching, (b) Inter-sentential switching and (c) intra-sentential switching. Six different functions of code-switching there were (a) quotation, (b) addressee specification, (c) interjection, (d) reiteration, (e) message qualification, and (f) personalization or objectification. The lecturer’s purposes used code-switching in the teaching-learning process was to explain the material that is difficult for students to understand, to help students understand the material in the target language, to strengthen understanding of new vocabulary, to inform, to translate and to build a relationship with students. Also, surprising findings; improved the pronunciation of new vocabulary words that are difficult for students to pronounce and helped students remember the material that has been studied. Keywords: code-switching, qualitative method, EFL.